Evaluation of The Implementation of Community-Based Independent Curriculum in Madrasah in The City of Tidore Islands - Adam, Adiana; Syawal, Zulkarnain; Djasman, Chaerunnisa H.; Akhsan, Sahjad,M.; Juliadarma, Minggusta (Golden Ratio of Social Science and Education, 2024)
This research evaluates the implementation of the Independent Community-Based Curriculum in Tidore Islands City madrasah, with a focus on the quality and suitability of the Madrasah Operational Curriculum (KOM) documents and the Mapping of Strengthening Character Education and Religious Risk Assessment (P5 P2RA). Through a qualitative approach with case study methods, this research involved four state madrasas as the main locations: MAN 1, MAN 2, MTsN 2, and MTsN 3. The results of the research showed that the level of suitability and quality of documents varied, with MAN 1 and MAN 2 having documents that superior to MTsN 2 and MTsN 3. The curriculum at these madrasah successfully integrates local cultural values, character education, and 21st century skills such as critical thinking and collaboration. However, the main challenges include a lack of supporting facilities and the need to increase teacher competency. Research recommendations include teacher training, strengthening facilities, and collaborating with the community. This research emphasizes the importance of curriculum relevance to local contexts to create more inclusive and contextual education.